(untitled) (Latakia University Journal -Medical Sciences Series, 2019)
شملت الدراسة 46 مريضاً (38 ذكر،8 إناث) مصاباً بتضيّق البواب الضخامي قبلوا وعولجوا في مشفى الأسد الجامعي باللاذقية بين عامي 1998-2007.متوسط عمر الرضيع في أثناء التشخيص هو 5-8 أسابيع,الوليدالأول ذو الزمرة O+هو الأكثر إصابة. أكثر الأعراض توارداً هو القياء النافوري وعدم كسب الوزن . والعلامة الأكثر مصادفة هي التجفاف, بينما لم تتجاوز نسبة تواجد الزيتونة البوّابية 60% . أهم مشعر مخبري هو ارتفاع البيكربونات لدى الرضيع (قلاء استقلابي). التصوير بالأمواج فوق الصوتية إجراء سهل وسريع ذو حساسية ونوعية عالية جداً في تشخيص تضيق البواب الضخامي. أهم المضاعفات استمرار القياء بعد الجراحة وخمج الجرح.متوسط مدة الإقامة في المشفى (6,5) يوماً، متوسط مدة الإقامة بعد الجراحة يومان. The study included 46 infants (38 males and 8 females) who had hypertrophic pyloric stenosis and who had been admitted and treated in Al-Assad University Hospital in Lattakia in 1998-2007. The mean age at diagnosis is 5-8 weeks. The first child with O+ is the most infected. The most famous symptoms are nonbilius projectile vomiting and weight loss. The most famous sign is dehydration, and the presence of pyloric olive is up to 60%.The most important laboratory test is increased bicarbonates (metabolic alkalosis). Echography is an easy and rapid procedure, and its quality and sensitivity are very high in HPS diagnosis. The most important complications are vomiting after surgery and wound infection. The mean hospitalization time is 6.5 days and the mean hospitalization time after surgery is 2 days.